2022
DOI: 10.1007/s42770-022-00686-5
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum Y15 alleviate type 2 diabetes in mice via modulating gut microbiota and regulating NF-κB and insulin signaling pathway

Abstract: Probiotics have been used for the treatment of chronic metabolic diseases, including type 2 diabetes (T2D). However, the mechanisms of antidiabetic effects are not well understood. The object of this study is to assess the antidiabetic effect of Lactiplantibacillus plantarum Y15 isolated from Chinese traditional dairy products in vivo. Results revealed that L. plantarum Y15 administration improved the biochemical indexes related to diabetes, reduced pro-inflammatory cytokines, L. plantarum Y15 administration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Further studies confirmed that this reduction was significantly related to its regulation of the GLUT-4 and IRS-1 expression. GLUT-4 is a transmembrane protein that binds to insulin and promotes glucose transport. , IRS-1 is the substrate of insulin receptor tyrosine kinase . With the binding of insulin and IRS-1, insulin receptor tyrosine kinase and IRS-1 will be phosphorylated, which then binds to the P85 subunit of PI3K and activates PI3K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies confirmed that this reduction was significantly related to its regulation of the GLUT-4 and IRS-1 expression. GLUT-4 is a transmembrane protein that binds to insulin and promotes glucose transport. , IRS-1 is the substrate of insulin receptor tyrosine kinase . With the binding of insulin and IRS-1, insulin receptor tyrosine kinase and IRS-1 will be phosphorylated, which then binds to the P85 subunit of PI3K and activates PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 IRS-1 is the substrate of insulin receptor tyrosine kinase. 37 With the binding of insulin and IRS-1, insulin receptor tyrosine kinase and IRS-1 will be phosphorylated, which then binds to the P85 subunit of PI3K and activates PI3K. The above processes promote the translocation of GLUT4 to the cell membrane and the transportation of glucose.…”
mentioning
confidence: 99%
“…The scientific literature is full of examples on how dietary supplementation with probiotic bacteria has a protective effect against the onset of some of the aforementioned diseases. Regarding T2D, probiotics have recently shown their benefits when administered in either animals , or humans, strengthening gut barrier function, reshaping gut microbiota composition, and lowering proinflammatory cytokines, such as interleukin (IL)-6, IL-8, and tumor necrosis factor (TNF)-α, while increasing anti-inflammatory ones like IL-10 and IL-4.…”
Section: Introductionmentioning
confidence: 99%
“…Promising results on glycemic control were also demonstrated by Naito et al in obese, prediabetic adults 9 . The mechanism by which probiotics may affect glycemic control is not well understood; suggested mechanisms include reduction of intestinal permeability, reduction of pro‐inflammatory cytokines and oxidative stress, regulation of nuclear factor κ B and insulin signaling pathway, and increased insulin sensitivity 10 . We are unaware of studies assessing the effect of probiotics on glycemic control in CF.…”
Section: Introductionmentioning
confidence: 99%